2023
DOI: 10.1002/suco.202200749
|View full text |Cite
|
Sign up to set email alerts
|

Performance of meta concrete panels subjected to explosive load: Numerical investigations

Abstract: Research on strengthening and retrofitting of concrete structures against explosive loading has recently received much attention. This paper proposes a new type of reinforcement for concrete panels to enhance their blast‐resistant capacity. The reinforcement structure is naturally optimized with continuous nonself‐intersecting surfaces, known as triply periodic minimal surface (TPMS)‐primitive scaffold. A numerical model is developed to investigate the performance of TPMS‐primitive reinforced concrete panels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…It is observed that the concrete layers in SSC slabs have crater failure and steel plates occur local deformation or buckling under the action of explosion. Nguyen‐Van et al 10 proposed a new type of reinforcement for concrete panels to enhance their blast‐resistant capacity. The reinforcement structure was naturally optimized with continuous nonself‐intersecting surfaces, known as triply periodic minimal surface (TPMS)‐primitive scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the concrete layers in SSC slabs have crater failure and steel plates occur local deformation or buckling under the action of explosion. Nguyen‐Van et al 10 proposed a new type of reinforcement for concrete panels to enhance their blast‐resistant capacity. The reinforcement structure was naturally optimized with continuous nonself‐intersecting surfaces, known as triply periodic minimal surface (TPMS)‐primitive scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the design parameters [42] and the effect of an enhanced coating layer [43] on the band-gap formulation and the response of the meta-concrete were described. More recent expressions of meta-concrete are found in [44], where the performance of a meta-concrete slab having embedded dual-resonant aggregate is evaluated, and in [45], where the response of meta-concrete panels subjected to an explosive load is studied. Another type of meta-materials concept for the same scope is a meta-sandwich panel, which was a previously proved idea for energy absorption [46] and blast protection [47,48], but is now examined and extended under the prism of the meta-materials theory.…”
Section: Introductionmentioning
confidence: 99%